Sunshine - MacDonald, Andrew; Boyle, Danny; Twentieth Century Fox (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2007)
It is the year 2057, the sun is dying and mankind faces extinction. Earth's last hope rests with a courageous crew of eight men and women on a mission to ignite the fading star with a massive nuclear weapon. Deep into their voyage, out of radio contact with Earth, their mission begins to unravel and they find themselves fighting not only for their lives, but for the future of us all
Title from title screen
Co-producer, Bernard Bellew ; camera, Alwin Kuchler ; editor, Chris Gill ; music, John Murphy, Underworld ; production designer, Mark Tildesley ; art directors, Gary Freeman, Stephen Morahan, Denis Schnegg ; costume designer, Suttirat Anne Larlarb ; sound, Tim Fraser, Tom Sayers, John Hayward
Casts : Cillian Murphy, Chris Evans, Rose Byrne, Michelle Yeoh
With Chinese and Malay subtitles
Keywords: Interstellar travel -- Drama; Space flight -- Drama; Nuclear weapons -- Drama; End of the universe -- Drama; Science fiction films